Numerical modeling for slope stability analysis: a case study of the landslide on RN12 at PK 119+000, Adekar, Béjaïa, Algeria - Bousbia, Badreddine; Goudjil, Kamel (Budownictwo i Architektura / Civil and Architectural Engineering, 2026)
One of the biggest geotechnical risks is landslides, particularly in areas with mountains and seismic activity. This study focuses on soil reinforcement to a variety of methods intended to enhance the mechanical or physical characteristics of the ground by adding inclusions that function in tension, compression, or bending, in light of the technical and financial constraints of conventional retaining wall systems. Among these methods, soil nailing has become a cutting-edge, practical, and flexible stabilization technique. Investigating landslide-induced slope failures and suggesting site-specific soil improvement strategies that increase safety and reduce displacements are the goals of this study. Because landslides occur frequently in the area, a slope along a road in the commune of ADEKAR in the Béjaïa province (Algeria), was chosen as the case study site for this investigation. Two-dimensional finite element analysis (FEA) was used to evaluate the slope’s stability. This study shows that using soil nailing reinforcement techniques in conjunction with numerical modeling is a viable and effective stabilization method.